2021
DOI: 10.1111/1744-7917.12938
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of zona pellucida domain protein Dusky in Tribolium castaneum

Abstract: The zona pellucida domain protein Dusky (Dy) plays a vital role in wing morphogenesis in insects, but little information on its function has been reported. In this study, we found that dy regulated wing cell size, larval and pupal duration, and the metabolism of amino acid and 20‐hydroxyecdysone in Tribolium castaneum. Using RNA‐seq, 413 differentially expressed genes were identified between physiological buffer‐injected and dy‐double‐stranded RNA‐treated larvae, including 88 downregulated genes and 325 upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…We found that RNAi-mediated knockdown of pio inhibited the pupation and eclosion in T. castaneum (Figures 4 and 5). As previously reported, the ZP proteins dusky, dusky-like and miniature were shown to have crucial roles in metamorphosis of T. castaneum (Li et al, 2017(Li et al, , 2016(Li et al, , 2022, supporting the role of Pio in insect metamorphosis. Insect metamorphosis is coordinately controlled by 20E and JH in opposite manners (Jindra et al, 2013;Yamanaka et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We found that RNAi-mediated knockdown of pio inhibited the pupation and eclosion in T. castaneum (Figures 4 and 5). As previously reported, the ZP proteins dusky, dusky-like and miniature were shown to have crucial roles in metamorphosis of T. castaneum (Li et al, 2017(Li et al, , 2016(Li et al, , 2022, supporting the role of Pio in insect metamorphosis. Insect metamorphosis is coordinately controlled by 20E and JH in opposite manners (Jindra et al, 2013;Yamanaka et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…On the third, fourth, and fifth days after injection, 10 larvae were collected from the ds‐ pio and ds‐ ver groups, respectively. Half of the samples were prepared as previously to detect 20E titer using an LTQ XL mass spectrometer system (Thermo Fisher Scientific Inc.) (Hikiba et al, 2013; Li et al, 2022). The other half of the samples were dissolved in a 1:1 mixture of methanol and ether (Sinopharm Chemical Reagent Co., Ltd.), and then homogenized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AtCYP18A1 was highly expressed in the wings of Aethina tumida , which had not been reported in other insects. However, in T. castaneum , the zona pellucida domain protein Dusky (Dy) was found to modulate 20E metabolism through CYP18A1 expression, to control wing morphogenesis 43 . Thus, we speculate that CYP18A1 may play an important role in the wing development of insects.…”
Section: Discussionmentioning
confidence: 88%
“…After centrifugation, the supernatants were dried and suspended with 200 μL methanol to measure 20-hydroxyecdysone (20E) titer using an LTQ XL mass spectrometer system (Thermo Fisher Scientific, Inc., San Jose, CA, USA). 35,36 The remaining samples were homogenized by dissolving a 1:1 mixture of methanol and ether. After adding n-hexane, shook the samples at 4 °C overnight, and then centrifuged them to acquire the supernatants.…”
Section: -Hydroxyecdysone and Jh Titer Assaymentioning
confidence: 99%